2015
DOI: 10.1371/currents.eogt.8b0b6fffc7b999b34bc4c8152edbf237
|View full text |Cite
|
Sign up to set email alerts
|

Use of ChemoFx® for Identification of Effective Treatments in Epithelial Ovarian Cancer

Abstract: Selection of appropriate chemotherapy, including identification of platinum resistance, is critical to effective management of advanced epithelial ovarian cancer (EOC). ChemoFx®, a multiple treatment marker (chemoresponse assay), has been developed to address this challenge and to improve outcomes in patients with advanced EOC. While much work has been done that has demonstrated the analytical validity of this assay, more recent studies have highlighted the unique clinical benefits offered by the assay. A pros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 29 publications
(51 reference statements)
0
9
0
Order By: Relevance
“…This innovative technology looks to overcome CSC chemotherapy resistance occurring in some cancers, and to prevent recurrence. Randomized, assay-directed clinical trials are currently ongoing against glioblastoma and epithelial ovarian cancer, with overall response rate as primary outcome measure (ClinicalTrials.gov numbers: NCT03632798, NCT03949283 and NCT03632798); The ChemoFX ® assay has been developed by the US company Helomics and is dedicated to gynaecological cancers 36 . Its endpoint is total DNA quantification.…”
Section: State-of-the-art: Assays Showing Significant Predictive Capacitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…This innovative technology looks to overcome CSC chemotherapy resistance occurring in some cancers, and to prevent recurrence. Randomized, assay-directed clinical trials are currently ongoing against glioblastoma and epithelial ovarian cancer, with overall response rate as primary outcome measure (ClinicalTrials.gov numbers: NCT03632798, NCT03949283 and NCT03632798); The ChemoFX ® assay has been developed by the US company Helomics and is dedicated to gynaecological cancers 36 . Its endpoint is total DNA quantification.…”
Section: State-of-the-art: Assays Showing Significant Predictive Capacitiesmentioning
confidence: 99%
“…The ChemoFX ® assay has been developed by the US company Helomics and is dedicated to gynaecological cancers 36 . Its endpoint is total DNA quantification.…”
Section: State-of-the-art: Assays Showing Significant Predictive Capacitiesmentioning
confidence: 99%
“…Such an approach formed the basis for early chemosensitivity assays using patient cells. 69,70 The use of more precise analytical methods, such as high-content imaging, to identify specifically the subpopulations of cells that are sensitive or resistant to drug treatment may require the creative generation of novel drug response evaluation criteria to correlate in vitro drug response with clinical efficacy. [71][72][73][74] In summary, we have made significant advances to an unprecedented level to model cancer with much greater accuracy for precision medicine, in moving from the use of simplistic monolayer culture methods to the use of primary tumor sources and sophisticated 3D systems.…”
Section: Development Of New Approaches To Assess Cellular Response Inmentioning
confidence: 99%
“…The ChemoFX assay utilizes a differential staining readout technique using DAPI staining combined with automated quantification of viable cells in 2D. Several prospective studies have been reported, which showed an increase in overall survival of 14 months using assay‐directed treatment for 262 ovarian cancer patients . In a smaller study using breast cancer biopsies, pathological complete response correlated with assay outcome in vitro and was found to achieve a sensitivity of 83.3% and 71.4% specificity .…”
Section: The Functional Approach: Chemoresponse Assaysmentioning
confidence: 99%